التنمية الريفية في المنطقة الساحلية - الرفاعي, عبد الهادي; شملص, عفيفة (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تعد عملية التنمية الريفية من الأولويات الهامة، لأي مجتمع يسعى إلى التطور والتقدم الاقتصادي والاجتماعي والحضاري، خاصة في البلدان النامية. وسورية باعتبارها إحدى هذه البلدان فإنها تسعى نحو التطور من خلال عملية التنمية الشاملة. وللوقوف على أهم جانب في عملية التنمية قمنا بدراسة التنمية الريفية في المنطقة الساحلية وكذلك حاولنا استعراض أهم الخصائص الاجتماعية والاقتصادية لسكان ريف المنطقة الساحلية ومن ثم انتقلنا إلى دراسة العوامل الأساسية للتنمية الريفية كتوفير مياه الشرب والكهرباء والصرف الصحي والخدمات الصحية، بعد ذلك قمنا بدراسة رغبة سكان ريف المنطقة الساحلية بالهجرة إلى المدينة حيث توصلنا إلى أن نسبة جيدة من سكان ريف المنطقة الساحلية يرغبون بالهجرة إلى المدينة حيث احتل هدف العمل المرتبة الأولى لأسباب الهجرة وكان في المرتبة الثانية التعليم. The process of rustic development is considered an important priority for any society that seeks economic, social and cultural development, especially in the developing countries. As one of these countries, Syria seeks to develop through the comprehensive development process. To stand on the most important side in the development process, we have studied the rural development in the country side of the coastal area. We have also tried to review the most important social and economic characteristics of the people who live in the country side of the coastal area. Then, we have moved to study the main factors for rural development, such as the availability of drinking water, electricity, sewerage, healthy services. After that we have studied the habitants' desire to emigrate to the city. We have noticed that a good rate of habitants in the coastal area wish to emigrate to the city, to seek work has occupied the first reason for emigration, and the second reason is education.